Engineering, quality, and experimental design - Grove, Daniel M (Longman, 1992)
Engineering, Quality and Experimental Design is a unique text which will aid design and production engineers in their efforts to improve quality and productivity. Keeping formulae to a minimum, the authors explain the fundamental ideas involved in planning efficient experiments and making good use of the results. The book presents the engineer with a coherent strategy for using experiments to support product and process engineering, drawing on real-life examples of engineering practice. The content has been inspired by the work of the Japanese engineer Genichi Taguchi, but the authors show how many of Taguchi's objectives can be accomplished using simpler methods and utilizing modern computer technology. Particular emphasis has been given to experiments which are aimed at improving quality by reducing variation. Provides a clear explanation of the important topics of quality testing and productivity improvement in engineering design and manufacture using the Taguchi method.